Peran Organisasi Profesi Kesehatan dalam Pencegahan dan Penanganan Pelanggaran Ringan Hukum Kesehatan - Hotmaria Hertawaty Sijabat (Jurnal Kesehatan, 2024)
Health professional organisations play a crucial role in the prevention and handling of minor health law violations. By implementing strict codes of ethics and standards of practice, as well as through the mechanism of honour boards or ethics committees, these organisations can evaluate and act on violations fairly and objectively. This helps maintain the integrity of the health profession and prevent further offences from occurring. In addition, continuing education and training conducted by these organisations ensures that their members are kept informed of the latest developments in health law and best practices. Through this approach, health professional organisations not only strengthen the professional competence of their members, but also promote high standards of ethics and professionalism in every aspect of healthcare.Role of Organisations, Health Professions, Prevention, Handling, Minor Violations, Health Law